Mean Reversion in Short-Horizon Expected Returns - Conrad, Jennifer; Kaul, Gautam (Review of Financial Studies, 1989)
This article develops and estimates a simple model for monthly expected stock returns that relies on the rapidly decaying structure of shorter-horizon (weekly) expected returns. The most striking aspect of our finds is that the rapid mean reversion in short-horizon expected returns implies much greater variation through time in monthly expected returns than has been documented in earlier studies. For instance, during the 1962 to 1985 period, over 25 percent of the return variance of small firms can be explained by time variation in expected returns.